Bicarbonate boosts flash response amplitude to augment absolute sensitivity and extend dynamic range in murine retinal rods - Adhikari, Rajan D.; Kossoff, Amanda M.; Cornwall, M. Carter; Makino, Clint L. (Frontiers in Molecular Neuroscience, 2023)
Rod photoreceptors in the retina adjust their responsiveness and sensitivity so that they can continue to provide meaningful information over a wide range of light intensities. By stimulating membrane guanylate cyclases in the outer segment to synthesize cGMP at a faster rate in a Ca2+-dependent fashion, bicarbonate increases the circulating “dark” current and accelerates flash response kinetics in amphibian rods. Compared to amphibian rods, mammalian rods are smaller in size, operate at a higher temperature, and express visual cascade proteins with somewhat different biochemical properties. Here, we evaluated the role of bicarbonate in rods of cpfl3 mice. These mice are deficient in their expression of functional cone transducin, Gnat2, making cones very insensitive to light, so the rod response to light could be observed in isolation in electroretinogram recordings. Bicarbonate increased the dark current and absolute sensitivity and quickened flash response recovery in mouse rods to a greater extent than in amphibian rods. In addition, bicarbonate enabled mouse rods to respond over a range that extended to dimmer flashes. Larger flash responses may have resulted in part from a bicarbonate-induced elevation in intracellular pH. However, high pH alone had little effect on flash response recovery kinetics and even suppressed the accelerating effect of bicarbonate, consistent with a direct, modulatory action of bicarbonate on Ca2+- dependent, membrane guanylate cyclase activity.